Analisis Penalaran Hakim Dalam Putusan Praperadilan (Studi Kasus Di Pengadilan Negeri Klas 1a Khusus Surakarta Tahun 2011-2012) - SUTARJO, Sutarjo; , Prof. Dr. Harun Joko Prayitno, M.Hum; , Dr. Aidul Fitriciada Azhari, SH., M.Hum (2015)
Pre-trial court is a new institution which was established simultaneously with the creation of Indonesian Criminal Procedure Code (Act No. 8 of 1981). Its authorities include determination of legality of an arrest or a detention; the legality of an investigation termination or a prosecution termination; legality of house entry, search and/or seizure; and restitution and rehabilitation for someone whose criminal case is discontinued at the level of investigation or prosecution. The objectives of this research are :(1) to explain why judges did not grant / reject the criminal pretrial suit submitted by the petitioners to the District Court of Surakarta over a span of two years back; and (2) to provide a guidance on how a pretrial petition shall be organized so that it is granted or accepted. This research used the descriptive analytical research method w th the juridical normative approach. The data of research consisted of primary and secondary es. They were collected through library research and research on law decided by the judges through the judicial process, and they were then analyzed by using the juridical normative/doctrinal model of analysis. The results of research show that (1) in the period of 2011-2012, none of the overall pretrial petitions submitted was granted or accepted by the judges of the District Court of Surakarta due to the non-fulfillment of administrative elements in the judicial process and that of the legal standing of both the petitioners and defendants; and (2) there is a need for analysis of reasoning for the etitioners so that that their pretrial petitions are granted/accepted by fulfilling all of the elements of pretrial litigation procedures.